Desenvolvimento de uma nova bebida funcional probiótica à base de melão Cantaloupe sonificado - Fonteles, Thatyane Vidal (2011)
The use of fruit juices for the development of functional foods has been an alternative for people who do not want or cannot make use of fermented dairy products. The objective of this research was the development of a drink with probiotic properties trough the fermentation of melon juice by Lactobacillus casei NRRL B-442. The first stage of the work consisted of the optimization of pH and temperature of fermentation for the L. casei cultivation in melon juice. Results showed that this strain has fermentative potential in melon juice, with no need of nutrient supplementation to reach the appropriated values of pH and viable cells. The best operating condition found to guarantee a good growth of the microorganism and ensure the cellular viability necessary for the product to be considered probiotic was the temperature of 31°C with initial pH of 6.1. The technological advantage of using melon juice as a substrate for probiotic fermentation was demonstrated in this work because the natural pH of the juice provided a favorable environment for the probiotic microorganism development. In a second stage, the effect of ultrasound treatment on quality parameters of melon juice was investigated as a function of intensity of ultrasonic energy and treatment time. The ultrasonic processing intensity using 372.93 W/cm2 for 10 minutes improved the quality of the juice reducing the spoilage due to enzyme activity, increasing homogeneity without damaging the product color. In the third phase of the research, the kinetics of probiotic melon juice fermentation and the influence of the product storage under refrigeration on the beverage quality parameters such as survival of L. casei, post-acidification and color were studied. The melon juice was subjected to ultrasonic processing (372.93 W/cm2/10min) and inoculated with 1% (v/v) and incubated at 31°C for 8 hours. The fermented juice was stored at 4°C, and pH, color, cell biomass, and viable cells number were evaluated. Analyses were performed at intervals of 7 days until 42 days of storage. The highest cell count was achieved within 12 hours of study, reaching 9.0 log CFU/mL, but from the 8th of fermentation there was no significant increase in the concentration of viable cells. Thus, 8 hours was elected as the optimal fermentation time to prepare the probiotic melon juice. During refrigerated storage there was acid production and a slight reduction in the number of viable cell. However, the product kept the number of viable cells above the level recommended by the current legislation during 42 days of storage at 4°C, regardless of having been stocked sugar-free or with sugar addition and no damage to the product color was observed. Melon juice was considered a good vehicle for probiotic microorganism as it showed viable cell count higher than 8 log CFU/mL throughout the studied period.